“It feels like an endless fight”: a qualitative study exploring healthcare utilization of persons with rheumatic conditions waiting for pain clinic admission - Nathan Blanchard; Simon Deslauriers; Jonathan Gervais-Hupé; Anne Hudon; Jean-Sébastien Roy; Sasha Bernatsky; Debbie E. Feldman; Anne Marie Pinard; Mary-Ann Fitzcharles; François Desmeules; Kadija Perreault (BMC Musculoskeletal Disorders, 2022)
Abstract Background Individuals living with a rheumatic pain condition can face delays in accessing pain clinics, which prevents them from receiving timely treatment. Little is known regarding their specific healthcare utilization in order to alleviate pain while waiting to obtain services in pain clinics. Hence, the aim of this study was to explore the perceptions and experiences of persons living with rheumatic conditions regarding healthcare utilization while waiting to access a pain clinic. Methods In this qualitative descriptive study, semi-structured interviews were conducted with adults living with a painful rheumatic condition that reported either being waiting for admission in a pain clinic, having been referred but then denied pain clinic services, or having received services during the previous six months, in the province of Quebec, Canada. The interviews were transcribed verbatim, and an inductive thematic analysis was performed. Results Twenty-six individuals were interviewed (22 women and 4 men; mean age 54 ± 10 years). Three themes were identified: 1) lacking guidance in identifying solutions to their complex and multidimensional needs, 2) struggling to obtain and maintain services due to systemic access barriers, and 3) displaying resilience through a search for accessible and sustainable self-management strategies. Conclusions The current approaches and structures of health services fail to adequately answer the service needs of individuals experiencing painful rheumatic conditions. Important shifts are required in pain education, in increasing access to multidisciplinary approaches at the primary care level and in breaking down barriers individuals with chronic pain face to receive appropriate and timely care.